2020
DOI: 10.1037/pac0000451
|View full text |Cite
|
Sign up to set email alerts
|

Emotional response to pictures of the armed conflict in Colombia.

Abstract: After a 5-decade armed conflict, a peace process was recently initiated in Colombia. Researchers of this conflict have frequently argued that decades of excessive mass-media exposure to conflict-related information have resulted in negative emotional outcomes in the Colombian population, which could be responsible for the observed apathy and disbelief regarding peace. Notwithstanding the relevance of these theoretical analyses, no experimental studies have explored the emotional response of the Colombian popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Higher levels of arousal are usually associated with low levels of dominance (Hurtado-Parrado et al, 2020). Due to the victims’ exposure to the armed conflict, it suggests emotional hyperreactivity to different types of social stimuli (positive, neutral, or negative).…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of arousal are usually associated with low levels of dominance (Hurtado-Parrado et al, 2020). Due to the victims’ exposure to the armed conflict, it suggests emotional hyperreactivity to different types of social stimuli (positive, neutral, or negative).…”
Section: Discussionmentioning
confidence: 99%
“…Second, to our knowledge, with a few exceptions (e.g., refs. 26 28 ), experimental studies have not used real-life images of graphic violence and they have largely examined outcomes quite different from those discussed above. One study showed bloody or gory images from the International Affective Pictures System (IAPS) ( 29 ); subjects were told they were real or were shown the same pictures with false Hollywood copyrights and told they were not real, and then were asked how negatively they felt about each of the images.…”
Section: Experimental Research On Media Exposure To Violencementioning
confidence: 99%
“…However, knowing how negative an image is scored is not the same as knowing how much distress a person experiences after seeing the image. A second study asked respondents to rate how pleasant and arousing IAPS images and images from the armed conflict in Columbia were using visual analog scales of happy/unhappy and sleepy/excited figures ( 27 ). Again, the affective valence assigned to an image is not equivalent to the experience of psychological distress evoked by an image.…”
Section: Experimental Research On Media Exposure To Violencementioning
confidence: 99%
“…While this short description should not be considered a comprehensive review of the different perspectives, it highlights how the different types of media have the potential to contribute to radicalization. An extensive literature distantly related to the topic of the current review has found that exposure to images related to terrorism, such as those depicted in the media, can have negative psychological effects (e.g., Felix et al, 2020 ; Hurtado‐Parrado et al, 2020 ). However, it remains under‐researched as to how the different types of exposure and interactions with different medias impact radical attitudes and behaviours specifically.…”
Section: Introductionmentioning
confidence: 99%